Mapping Sustainability across the World: Signs, Challenges and Opportunities for Democratic Countries - Bogdan Ștefanachi (Sustainability, 2022)
This article aims to create the nexus between sustainable development and the quality of the political regime. The study aims to respond to the following research questions: “how could influence the quality of the democracy the dynamics of the Sustainable Development Goals (SDGs 17)?” and “what are the premises for sustainable development in the new political context, characterized by democratic recession?” The purpose of the study is to underline the fact that democratic regimes are inclined to create both participative and deliberative frames for achieving the SDGs in accordance with UN 2030 Agenda. The research methodology used in this study is based on descriptive and inferential statistics. The research data are collected from secondary sources in the years between 2015 and 2021, from 193 countries covering all the geographical areas. The empirical results suggest two models of development: the Asian model of sustainable development characterized by economic growth and the Western democratic model based on democratic institutions, fair justice and mechanisms for preserving peace. We noticed that the key-variables for explaining the dynamics of sustainability in correlation with democratic index are represented by the functioning of the governments and the political participation. Through civic engagement and political accountability, democracy could be seen as a pre-requisite for achieving an optimal level of the SDGs. All these empirical results could prove valuable for the scholars interested in the relation between democracy and sustainability and for the political decision makers involved in shaping strategies for social, economic and environmental development.